AMOEBA-BASED NEUROCOMPUTING WITH CHAOTIC DYNAMICS. - Aono, Masashi; Hara, Masahiko; Aihara, Kazuyuki (Communications of the ACM, 2007)
This article describes amoeba-based neurocomputing as a deadlock-breaking form of parallel computing used to search for reasonable solutions. The contraction-relaxation rhythmic oscillations of this unicellular organism uses shape deformations as an integrated computational capacity. The article discusses experiments in which a neural network is modeled on the amoeba's photoavoidance-based shape deformation under optical feedback control. This system is the first non-silicon based implementation of chaotic neural computing. The capability of spontaneously escaping from equilibrium and stability is essential for our biologically inspired computing, and amoeba chaotic dynamics achieve that.